Numerical modeling of the electrohydrodynamic effect to natural convection in vertical channels - Kasayapanand N. (2014)
The electrohydrodynamic effect to natural convection inside the vertical channels is numerically investigated by computational fluid dynamics technique. The range of parameters considered are 104 = Ra = 107, 7.5 = V0 = 17.5 kV, and 2 = aspect ratio = 10. Flow and temperature distributions are affected with supplied voltage at the wire electrodes, and the heat transfer enhancement is significantly influenced at low Rayleigh number. The augmented volume flow rate of fluid is indicated in relation with the number of electrodes. Moreover, heat transfer enhancement also depended on the electrode arrangement while the number of electrodes is initially fixed. The relation between channel aspect ratio and number of electrodes that performs the maximum heat transfer is expressed incorporating with the optimum concerning parameters. © 2006 Elsevier Ltd. All rights reserved.